2020
DOI: 10.3324/haematol.2020.246603
|View full text |Cite
|
Sign up to set email alerts
|

Donor sex, age and ethnicity impact stored red blood cell antioxidant metabolism through mechanisms in part explained by glucose 6-phosphate dehydrogenase levels and activity

Abstract: Red blood cell storage in the blood bank promotes the progressive accumulation of metabolic alterations that may ultimately impact the erythrocyte capacity to cope with oxidant stressors. However, the metabolic underpinnings of the capacity of RBCs to resist oxidant stress and the potential impact of donor biology on this phenotype are not known. Within the framework of the REDS-III RBC-Omics study, RBCs from 8,502 healthy blood donors were stored for 42 days and tested for their propensity to hemolyze followi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
140
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(151 citation statements)
references
References 46 publications
10
140
0
1
Order By: Relevance
“…Of note, sex-and age-dependent changes in these pathways have been recently reported. 25 In particular, increased purine oxidation or impaired activation of the PPP have been negatively associated with the capacity of stored RBCs to circulate upon transfusion. 46 Here we expand on these observations by describing an impact of the age of RBC subpopulations on these pathways.…”
Section: Metabolomics Of Rbcs After Separationmentioning
confidence: 99%
See 2 more Smart Citations
“…Of note, sex-and age-dependent changes in these pathways have been recently reported. 25 In particular, increased purine oxidation or impaired activation of the PPP have been negatively associated with the capacity of stored RBCs to circulate upon transfusion. 46 Here we expand on these observations by describing an impact of the age of RBC subpopulations on these pathways.…”
Section: Metabolomics Of Rbcs After Separationmentioning
confidence: 99%
“…34,[62][63][64] of senescent RBCs within a RCC will presumptively have higher accumulation of side products of aging/lysis that undoubtedly affect the quality of the whole RCC unit. Other studies have discussed the impact of donor age and sex on both the quality characteristics of RCCs during in vitro storage 22,25,28,65 and the transfusion efficacy, [66][67][68][69] with an increased risk of mortality due to sex-mismatched transfusions. [70][71][72][73][74] fRBCs stored in vitro have generally shown superior quality measures, such as less susceptibility to storage-induced hemolysis and mechanical fragility, and better rheologic properties compared to mRBCs 22,75 that can be related to a larger proportion of biologically younger RBCs in female donors.…”
Section: Intracellular Reactive Oxygen Species and Ca 2+ In Rbcs Dumentioning
confidence: 99%
See 1 more Smart Citation
“…Of note, age and sex significantly affect RBC metabolism in healthy blood donors with respect to energy and redox metabolism. 20 As such, we hypothesized that RBC metabolic differences in COVID-19 patients could contribute to their ability to cope with oxidant stress and hypoxemia and, as such, to the heterogeneity of disease expression. In addition to these considerations, preliminary data were offered by others for peer-review supporting a potential direct structural interaction between SARS-CoV-2 proteins and hemoglobins; 19 if validated, this would provide a direct role for the virus in compromising RBC oxygen transport and delivery.…”
Section: Introductionmentioning
confidence: 99%
“…The extent of the lesions observed is variable among red cell concentrates (RCCs), which could indicate either a process-or a donor-dependency (Jordan et al, 2016;Tzounakas et al, 2016;Kanias et al, 2017;D'Alessandro et al, 2020). More particularly, it was observed that the initial oxygenation saturation (sO 2 ) levels did widely vary among RCCs.…”
Section: Introductionmentioning
confidence: 99%